2018
DOI: 10.1021/acs.inorgchem.7b03132
|View full text |Cite
|
Sign up to set email alerts
|

Negative Photochromism Based on Molecular Diffusion between Hydrophilic and Hydrophobic Particles in the Solid State

Abstract: A colored hybrid based on a merocyanine adsorbed in a nanoporous-silica-composed dendritic fibrous silica was prepared by adsorption onto the nanoporous silica from a spiropyran solution during UV irradiation (photoinduced adsorption). The obtained red hybrid thus exhibited negative photochromism by visible-light irradiation. The hybrid was further combined with an organophilic clay by a solid-state mixing without using solvent to achieve excellent reversibility of the color change, which was thought to be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 34 publications
3
19
0
5
Order By: Relevance
“…Correspondingly,t he isomerization of the previously introduced spiropyrans (SP,see Section 2.1) into merocyanine (MC) can not only be induced by mechanical forces,but also by,f or example,t emperature,p H, solvation, or light. [193][194][195][196][197][198][199][200] Intriguingly,S P-based self-reporting systems have been developed that respond to several stimuli simultaneously. [46][47][201][202][203][204] Forexample,Qui et al reported the synthesis of poly(hydroxyethyl acrylate) with incorporated SPs,w hich changed color upon light irradiation or swelling in water.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly,t he isomerization of the previously introduced spiropyrans (SP,see Section 2.1) into merocyanine (MC) can not only be induced by mechanical forces,but also by,f or example,t emperature,p H, solvation, or light. [193][194][195][196][197][198][199][200] Intriguingly,S P-based self-reporting systems have been developed that respond to several stimuli simultaneously. [46][47][201][202][203][204] Forexample,Qui et al reported the synthesis of poly(hydroxyethyl acrylate) with incorporated SPs,w hich changed color upon light irradiation or swelling in water.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Correspondingly, the isomerization of the previously introduced spiropyrans (SP, see Section 2.1) into merocyanine (MC) can not only be induced by mechanical forces, but also by, for example, temperature, pH, solvation, or light. [ 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 ] Intriguingly, SP‐based self‐reporting systems have been developed that respond to several stimuli simultaneously. [ 46 , 47 , 201 , 202 , 203 , 204 ] For example, Qui et al.…”
Section: Stimuli‐responsive Self‐reporting Polymeric Materialsmentioning
confidence: 99%
“…Abbott und Mitarbeiter machten sich solche selbstberichtenden LCs zunutze und erweiterten das Konzept durch die Einführung selbstregulierender Eigenschaften. [192] [193][194][195][196][197][198][199][200] Interessanterweise sind SP-basierte selbstberichtende Systeme entwickelt worden, die auf mehrere Stimuli gleichzeitig reagieren. [46,47,[201][202][203][204] Qui et al berichteten zum Beispiel über die Synthese von Poly(hydroxyethylacrylat) mit eingebauten SPs,d ie bei Lichteinstrahlung oder Schwellung in Wasser ihre Farbe änderten.…”
Section: Angewandte Chemieunclassified
“…Dementsprechend kann die Isomerisierung der zuvor eingeführten Spiropyrane (SP) (siehe Abschnitt 2.1) zu Merocyanin (MC) nicht nur durch mechanische Kräfte, sondern z. B. auch durch Temperatur, pH‐Wert, Solvatation oder Licht induziert werden [193–200] . Interessanterweise sind SP‐basierte selbstberichtende Systeme entwickelt worden, die auf mehrere Stimuli gleichzeitig reagieren [46, 47, 201–204] .…”
Section: Stimuliresponsive Selbstberichtende Polymere Materialienunclassified
“…В результате ранее выполненных исследований показана возможность получения фотохромных систем с обратным фотохромизмом на основе дендримерных наночастиц диоксида кремния и нитро- [2,3], а также гидроксизамещенных индолиновых спиропиранов [4,5]. Обратный фотохромизм наночастиц диоксида кремния обнаружен и при использовании катионных спиропиранов [6].…”
Section: Introductionunclassified